A new species of Trichomycterus (Siluriformes: Trichomycteridae) from the upper río Magdalena basin, Colombia - García-Melo, Luis J.; Villa-Navarro, Francisco A.; Donascimiento, Carlos (Zootaxa, 2016)
Trichomycterus tetuanensis, new species, is described from the río Tetuan, upper río Magdalena basin in Colombia. The new species is distinguished by its margin of caudal fin conspicuously emarginate, in combination with a high number of opercular odontodes (21–39), reflected externally in the large size of the opercular patch of odontodes, 3 irregular rows of conic teeth in the upper jaw, 42–52 interopercular odontodes, 8 branchiostegal rays, 37 post Weberian vertebrae, 7 branched pectoral-fin rays, hypural 3 separated from hypural plate 4+5, and background coloration light brown with darker dots uniformly sparse on dorsum and sides of trunk. Some apomorphic characters informative for the phylogenetic affinities of the new species within Trichomycterus are discussed.